2012
DOI: 10.5402/2012/609718
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis Disease Diagnosis Using Hybrid Case Based Reasoning and Particle Swarm Optimization

Abstract: Correct diagnosis of a disease is one of the most important problems in medicine. Hepatitis disease is one of the most dangerous diseases that affect millions of people every year and take man’s life. In this paper, the combination of two methods of PSO and CBR (case-based reasoning) has been used to diagnose hepatitis disease. First, a case-based reasoning method is workable to preprocess the data set therefore a weight vector for every one feature is extracted. A particle swarm optimization model is then pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
1
16
0
3
Order By: Relevance
“…We now compare our results with other studies [4] as shown in Table 5. It is evident from the table that our method offers comparable results with 80 simulations at present.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…We now compare our results with other studies [4] as shown in Table 5. It is evident from the table that our method offers comparable results with 80 simulations at present.…”
Section: Resultssupporting
confidence: 59%
“…We use multiple imputation technique for missing values in the data set. This is a novel approach compared to the previous studies on hepatitis disease diagnosis [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Gradient descent technique has been used to optimize a model to solve the problem of feature selection, called grafting [9]. Similarity measurement in this research was using weighted Euclidean distance method.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is very hard to get an appointment from a specialist; it may take some days, week or months as well. Most likely, the disease may have affected the patient most before the patient refers to the specialist for diagnosis [4]. Most of the high-risk disorders could be treated only in the initial stage.…”
Section: Introductionmentioning
confidence: 99%